The Hertel classification can’t predict the risk of humeral head osteonecrosis after osteosynthesis using an anterolateral approach - Cruz, Márcio Alves; Mouraria, Guilherme Grisi; Kikuta, Fernando Kenji; Zogbi, Daniel Romano; Coelho, Sérgio de Paula; Etchebehere, Maurício (Clinics, 2023)
Background: Proximal humeral fractures can progress to osteonecrosis of the humeral head. Hertel developed a binary classification system (12 subtypes) and demonstrated that some patterns have more risk to develop osteonecrosis. Hertel described the prevalence and the risk factors for Humeral head osteonecrosis after osteosynthesis using a Deltopectoral approach. Few studies have evaluated the prevalence and the capacity of Hertel's classification to predict Humeral Head osteonecrosis following osteosynthesis of proximal Humeral fractures through the anterolateral approach. The objectives of this study were to correlate osteonecrosis predictors established by the Hertel classification with the risk of developing osteonecrosis and its prevalence after osteosynthesis using the anterolateral approach. Methods: This was a retrospective study of patients who underwent osteosynthesis of proximal humerus fractures using an anterolateral approach. Patients were divided into two groups: high risk for necrosis (group 1) and low risk for necrosis (group 2) according to Hertel's criteria. The overall prevalence of osteonecrosis and the prevalence in each group were calculated. A radiological examination was performed in the true anteroposterior (Grashey), scapular, and axillary views, before and after the operation (minimum 1 year after surgery). A Kaplan-Meier curve was used to assess the pattern of the temporal evolution of osteonecrosis. The groups were compared using the Chi-square test or Fisher's exact test. The unpaired t-test (parametric variables – age) and the Mann-Whitney test (non-parametric time between trauma and surgery) were used. Results: In total, 39 patients were evaluated. The postoperative follow-up time was 14.5 ± 3.3 months. The time to onset of necrosis was 14.1 ± 3.9 months. Sex, age, and time between trauma and surgery did not influence the risk of necrosis. Type 2, 9, 10, 11, and 12, or fractures with posteromedial head extension less than or equal to 8 mm, or diaphysis deviation greater than 2 mm, as well as grouping did not influence the risk for osteonecrosis. Conclusions: Hertel's criteria were not able to predict the development of osteonecrosis after osteosynthesis of proximal humerus fractures performed through the anterolateral approach. The total prevalence of osteonecrosis was 17.9% with a tendency toward an increased incidence after 1 year of surgical treatment.